Effectiveness of Active Compounds in Pineapple Peel Extract (Ananas comosus) as a Biolarvicide Against Aedes aegypti: Integration of In Silico, In Vitro, and Comprehensive Literature Review Analyses - Defri Defri; M. Yulis Hamidy; Elva Susanty (PSPP JOURNALS, 2026)
Dengue hemorrhagic fever remains an important public health problem in tropical countries, including Indonesia, and larval control of Aedes aegypti is a strategic component of dengue prevention. This revised manuscript aims to synthesize published evidence on the larvicidal potential of pineapple peel and other pineapple waste preparations against Aedes aegypti larvae. In response to methodological concerns, the study design was clarified as a semi-systematic literature review with narrative synthesis; it does not report original in silico docking or original in vitro larval bioassay experiments. Literature was identified from indexed scientific sources and the manuscript reference set using predefined keywords related to Ananas comosus, pineapple peel, biolarvicide, larvicidal activity, Aedes aegypti, mortality, LC50, phytochemicals, and mechanism of action. Eligible studies were original articles reporting larval mortality, LC50/LC90, concentration-response patterns, or relevant phytochemical and mechanistic findings. The reviewed evidence indicates that pineapple peel preparations contain bioactive compounds such as flavonoids, saponins, tannins, alkaloids, triterpenoids, and bromelain, which may contribute to larval toxicity through respiratory disruption, digestive interference, neurophysiological disturbance, antifeedant effects, and proteolytic tissue damage. Ethanol-based pineapple peel extracts and flavonoid fractions showed the most promising activity in the cited studies, although the strength of evidence remains limited by methodological heterogeneity, limited numbers of comparable studies, and the absence of standardized bioassay protocols. Pineapple peel waste therefore has potential as an eco-friendly larvicidal source, but further standardized laboratory validation, non-target toxicity assessment, formulation development, and field evaluation are required before practical implementation.